2015
DOI: 10.1002/lsm.22389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a preceding fractional carbon dioxide laser on the outcome of combined local narrowband ultraviolet B and topical steroids in patients with vitiligo in difficult‐to‐treat areas

Abstract: This study demonstrates that adding fractional CO2 laser treatment to NB-UVB phototherapy and topical steroids improves the repigmentation rate of vitiliginous lesions on hands in some patients. This technique may be offered to vitiligo patients who are unresponsive to other treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 24 publications
4
82
3
Order By: Relevance
“…found that monthly sessions for 3 months of fractional CO 2 laser treatment followed by 2‐hour sunlight exposure on daily basis result in improvement in vitiligo, which was assessed by the physician and by patient's satisfaction. Another studies reported by Vachiramon et al and Li et al also confirmed the superior result of triple combination of fractional CO 2 laser, NB‐UVB, and topical steroids in improvement of vitiligo in recalcitrant areas when compared to NB‐UVB and topical steroid, without any serious side effects.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…found that monthly sessions for 3 months of fractional CO 2 laser treatment followed by 2‐hour sunlight exposure on daily basis result in improvement in vitiligo, which was assessed by the physician and by patient's satisfaction. Another studies reported by Vachiramon et al and Li et al also confirmed the superior result of triple combination of fractional CO 2 laser, NB‐UVB, and topical steroids in improvement of vitiligo in recalcitrant areas when compared to NB‐UVB and topical steroid, without any serious side effects.…”
Section: Discussionsupporting
confidence: 90%
“…This includes ablative laser and fractional laser devices. According to previous studies, incorporating laser treatment to the conventional treatments of vitiligo such as topical therapy or phototherapy resulted in higher degree of repigmentation than conventional treatment alone …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result from our study that shows 50 % of lesions treated with combined fractional CO 2 laser achieved more than 50 % repigmentation, compared to 23 % from previous study [10]. This may be due to the differences in anatomical location of the vitiliginous lesions.…”
Section: Discussioncontrasting
confidence: 76%
“…This includes ablative laser and fractional laser devices. According to previous studies, incorporating laser treatment to the conventional treatments of vitiligo such as topical therapy or phototherapy resulted in higher degree of repigmentation than conventional treatment alone, especially in difficult to treat areas such as bony prominence and extremities [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 95%